Predictors of sequence capture in a large-scale anchored phylogenomics project - Nunes, Renato; Storer, Caroline; Doleck, Tenzing; Kawahara, Akito Y.; Pierce, Naomi E.; Lohman, David J. (Frontiers in Ecology and Evolution, 2022)
Next-generation sequencing (NGS) technologies have revolutionized phylogenomics by decreasing the cost and time required to generate sequence data from multiple markers or whole genomes. Further, the fragmented DNA of biological specimens collected decades ago can be sequenced with NGS, reducing the need for collecting fresh specimens. Sequence capture, also known as anchored hybrid enrichment, is a method to produce reduced representation libraries for NGS sequencing. The technique uses single-stranded oligonucleotide probes that hybridize with pre-selected regions of the genome that are sequenced via NGS, culminating in a dataset of numerous orthologous loci from multiple taxa. Phylogenetic analyses using these sequences have the potential to resolve deep and shallow phylogenetic relationships. Identifying the factors that affect sequence capture success could save time, money, and valuable specimens that might be destructively sampled despite low likelihood of sequencing success. We investigated the impacts of specimen age, preservation method, and DNA concentration on sequence capture (number of captured sequences and sequence quality) while accounting for taxonomy and extracted tissue type in a large-scale butterfly phylogenomics project. This project used two probe sets to extract 391 loci or a subset of 13 loci from over 6000 butterfly specimens. We found that sequence capture is a resilient method capable of amplifying loci in samples of varying age (0-111 years), preservation method (alcohol, papered, pinned), and DNA concentration (0.020 ng/µl - 316 ng/ul). Regression analyses demonstrate that sequence capture is positively correlated with DNA concentration. However, sequence capture and DNA concentration are negatively correlated with sample age and preservation method. Our findings suggest that sequence capture projects should prioritize the use of alcohol-preserved samples younger than 20 years old when available. In the absence of such specimens, dried samples of any age can yield sequence data, albeit with returns that diminish with increasing age.